ANALISIS USAHATANI DAN SALURAN PEMASARAN KEMBANG KOL DI DESA BELENDUNG, KECAMATAN KLARI, KABUPATEN KARAWANG JAWA BARAT - Evi Sumiati; Rini Setyowati; Tungga Buana Diana (Fakultas Pertanian Universitas Borobudur, 2020)
The purpose of this study was to analyze the existing marketing margins in the cauliflower farm in Belendung Village. Analyzing the existing marketing channels in the cauliflower farm in Belendung Village. Analysis of cauliflower farm income on a 0.32 hectare land, the R / C value is 1.8. This indicates that cauliflower farming is profitable or feasible to be developed by farmers. The marketing process of cauliflower from farmers to consumers involves collecting traders, wholesalers and retailers. There are three cauliflower marketing channels in Belendung Village. The largest total profit to cost ratio for each cauliflower marketing channel was channel I at 1.8, channel II at 2.9 and channel III at 3.9. Channel III is the most profitable channel for farmers because it has the highest ratio value. Keywords : Cauliflower, Farming